The Integration Beetwen Religion and Philosophy According to Ibn Thufail and Ibn Rushd - Fahim Khasani (Aqlania: Jurnal Filsafat dan Teologi Islam, 2020)
Some scholars used to believe that Religion and Philosophy are conflictual, disharmonious and impossible to integrate. This opinion comes from two groups; textualists who do not care about philosophy and philosophy enthusiasts who ignore the creed. Both of them cannot be expected to contribute to the people in terms of developing knowledge and advancing knowledge. Then, came a third party who carefully saw the correspondence between Religion and Philosophy, even though the two could not be separated from each other. This simple article intends to present the efforts of two great philosophers from the Maghrib; Ibn Thufail (d 581 H) and Ibn Rushd (d 595 H) in harmonizing and integrating Religion and Philosophy / Revelation and Intellect / Faith and Science.